Strong High Pressure Systems Influencing the Weather in Poland During the Period 1971-2000 - Bielec-Bąkowska, Zuzanna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
This paper shows preliminary results of research into the occurrence of strong anticyclonic systems that influenced the weather in Poland during the period 1971–2000. The study was based on NCEP/NCAR reanalysis data, including daily values of the 1000 and 500 hPa geopotential heights, maps of mentioned geopotential heights and maps of sea-level field pressure. With the use of these data a number of exceptionally strong high-pressure systems were identified, together with their areas of origin and subsequent development patterns. They were then broken down into five groups with similar dynamics. The numbers of systems in each group were not found to follow any significant change trends in the long term. The greatest differences between groups were identified in terms of their annual occurrence rates and centre pressure values.
Keywords: atrong high pressure systems; atmospheric circulation; long-term variability; reanalyses